PERAN KEPERCAYAAN DALAM MEMEDIASI PENGARUH KUALITAS PRODUK DAN NILAI TERHADAP NIAT BELI ULANG PRODUK HIJAU (STUDI PADA PRODUK KOPI MEREK STARBUCKS) - pinaria, ni wayan chintia; Sukaatmadja, I Putu Gde; Yudi Setiawan, Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The objective of the research is to know the role of trust in mediating the effect of product quality and value on the repurchase intention of buying green products (study on Starbucks coffee). Consumers who have purchased Starbucks coffee are the study population. The technique of determining the sample was done by using purposive sampling method with 130 respondents. Questionnaire as research instrument and analysis technique used is Partial Least Square with Sobel Test. Based on the result of research, green perceived quality and green perceived value have positive and significant effect on trust and repurchase intention. Furthermore, it was found an important role of trust that not only directly affects repurchase intention but also significantly mediates the effect of green perceived quality and green perceived value ??on repurchase intentions.